ANALISIS PERUBAHAN KOMPONEN KIMIA KERIPIK BAYAM HIJAU (Amaranthus tricolor.L) AKIBAT PROSES PENGGORENGAN - Kasmira, Kasmira; Lahming, Lahming; Fadilah, Ratnawaty (Universitas Negeri Makassar, 2018)
This study aims to determine changes in the chemical content on green spinach chips processed in a way by frying pan. This research is a quantitative research (experimen) on samples of green spinach and green spinach chips. The analysis technique used is t test one sample which is processed using SPSS version 22.0. Chemical content observed on this study are iron, nitrate, nitrite, oxalate, calcium, antioxidants, and water content. The results showed that chips spinach green contained calcium (0.18%) and antioxidants (32.81%) were high